"Toilet Paper Panic": Uncertainty and Insecurity in Early 1970s Japan. Issue 2 (7th July 2021) - Siniawer, Eiko Maruko
Abstract: When toilet paper disappeared from store shelves across Japan in November 1973, the housewives who searched their neighborhood markets and stood in long lines for the scarce packs were described as unwitting perpetrators of a "toilet paper panic." The word "panic" evoked well-established notions of a social frenzy, irrational and overwrought. This article overturns a conception of panic laden with condescension and adopts, instead, a more empathetic approach to examining why a run on toilet paper and other daily necessities occurred in late 1973, and why it resonated so deeply across Japan as a "panic." In the broader context of the early 1970s, the toilet paper scare and its characterization as a "panic" can be understood as responses to sweeping and multifaceted economic challenges that destabilized daily life and threatened to upend middle-class lifestyles. After more than fifteen years of high economic growth, that sense of middle-class comfort and security was shaken by shortages and inflation as well as mounting evidence of government ineptitude and corporate profiteering. Buffeted by insecurity and uncertainty, Japanese "middle-classness" as both an experience and an ideal had never seemed as vulnerable as it did in the early 1970s.